Comparative potency of obeticholic acid and natural bile acids on FXR in hepatic and intestinal in vitro cell models. Issue 6 (5th November 2017) - Zhang, Yuanyuan; LaCerte, Carl; Kansra, Sanjay; Jackson, Jonathan P.; Brouwer, Kenneth R.; Edwards, Jeffrey E.
Abstract: Obeticholic acid (OCA) is a semisynthetic farnesoid X receptor (FXR) agonist, an analogue of chenodeoxycholic acid (CDCA) which is indicated for the treatment of primary biliary cholangitis (PBC) in combination with ursodeoxycholic acid (UDCA). OCA efficiently inhibits bile acid synthesis and promotes bile acid efflux via activating FXR‐mediated mechanisms in a physiologically relevant in vitro cell system, Sandwich‐cultured Transporter Certified ™ human primary hepatocytes (SCHH). The study herein evaluated the effects of UDCA alone or in combination with OCA in SCHH. UDCA (≤100 μmol/L) alone did not inhibit CYP7A1 mRNA, and thus, no reduction in the endogenous bile acid pool observed. UDCA ≤100 μmol/L concomitantly administered with 0.1 μmol/L OCA had no effect on bile acid synthesis beyond what was observed with OCA alone. Furthermore, this study evaluated human Caco‐2 cells (clone C2BBe1) as in vitro intestinal models. Glycine conjugate of OCA increased mRNA levels of FXR target genes in Caco‐2 cells, FGF‐19, SHP, OSTα/β, and IBABP, but not ASBT, in a concentration‐dependent manner, while glycine conjugate of UDCA had no effect on the expression of these genes. The results suggested that UDCA ≤100 μmol/L did not activate FXR in human primary hepatocytes or intestinal cell line Caco‐2. Thus, co‐administration of UDCA with OCA did not affect OCA‐dependent pharmacological effects.